Prevalence of Dental Anxiety among 5- to 8-Year-Old Taiwanese Children - Chen-Yi Lee, MS; Yong-Yuan Chang, ScD; Shun-Te Huang, DDS (Blackwell Synergy, 2007)
Many people experience discomfort to a greater or lesser degree about the prospect of dental treatment.